Design of the Test System for the Ability to Withstand the Overload Current of the Low Voltage Control Equipment Applied in Coal Mines. Issue 2 (May 2020) - Zhang, Hongkui; Ni, Rui; Zhu, Shuming
Abstract: On the basis of the development prospect of energy industry and the safety production situation of coal mine, the composition structure and working principle of low-voltage control equipment applied in coal mines were analyzed, and the electric power and thermal effect theory of low-voltage control equipment applied in coal mine were studied, and the design scheme of overload resistance test system was put forward, meanwhile, the flameproof electromagnetic starter for coal mines was tested according to the coal industry standard. The test results show that the design of the overload tolerance is reasonable.